Plant-specific cochaperone SSR1 affects root elongation by modulating the mitochondrial iron-sulfur cluster assembly machinery - Feng, Xuanjun; Hu, Yue; Xie, Tao; Han, Huiling; Bonea, Diana; Zeng, Lijuan; Liu, Jie; Ying, Wenhan; Mu, Bona; Cai, Yuanyuan; Zhang, Min; Lu, Yanli; et al. (PLoS genetics, 2025)
To elucidate the molecular function of SHORT AND SWOLLEN ROOT1 ( SSR1 ), we screened for su ppressors of the s sr1-2 ( sus ) was performed and identified over a dozen candidates with varying degrees of root growth restoration. Among these, the two most effective suppressors, sus1 and sus2 , resulted from G87D and T55M single amino acid substitutions in HSCA2 (At5g09590) and ISU1 (At4g22220), both crucial components of the mitochondrial iron-sulfur (Fe-S) cluster assembly machinery. SSR1 displayed a robust cochaperone-like activity and interacted with HSCA2 and ISU1, facilitating the binding of HSCA2 to ISU1. In comparison to the wild-type plants, ssr1-2 mutants displayed increased iron accumulation in root tips and altered expression of genes responsive to iron deficiency. Additionally, the enzymatic activities of several iron-sulfur proteins and the mitochondrial membrane potential were reduced in ssr1-2 mutants. Interestingly, SSR1 appears to be exclusive to plant lineages and is induced by environmental stresses. Although HSCA2 G87D and ISU1 T55M can effectively compensate for the phenotypes associated with SSR1 deficiency under favorable conditions, their compensatory effects are significantly diminished under stress. Collectively, SSR1 represents a new and significant component of the mitochondrial Fe-S cluster assembly (ISC) machinery. It may also confer adaptive advantages on plant ISC machinery in response to environmental stress.